Nigeria's import control under regionalism: the colonial Northern Nigerian experience, 1954-1960 (2021)
The colonization of Nigeria by the British opened a new vista in the history of the country. Colonial administrative structures in northern Nigeria included, native courts, native authorities, native treasury and a protectorate. Historians, political scientists, sociologists, economists and scholars of various disciplines have interrogated northern Nigerian history. Indirect rule System, colonial infrastructure, the rise of nationalism and colonial System of education are typical examples of northern Nigeria’s colonial experience. Similarly, scholars have made attempts at interrogating various aspects of the region’s colonial history. These include, colonial agricultural policies, colonial export control policies, marketing boards, trade restrictions, politics of decolonization, politics of transfer of power, constitutional developments, regionalism, nationalist movements, colonial tariff System and issues that deal with northern Nigeria. These intellectual efforts have not beamed their searchlight on how import control under regionalism was used as one of the strategies of decolonization process in northern Nigeria. It is against this backdrop that this paper interrogates import control as an economic policy which aided the entrenchment of regionalism in northern Nigeria. Import control under regionalism therefore became one of the strategies used by the colonial government in the devolution of some of its economic powers to the northern Nigerian region.